2016
DOI: 10.1111/1475-6773.12512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Parent‐Reported Medical Home Status on Children's Health Care Utilization, Expenditures, and Quality: A Difference‐in‐Differences Analysis with Causal Inference Methods

Abstract: Having a medical home may help improve health care quality for children; losing a medical home may lead to higher utilization of emergency care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Family members, however, may not be aware of all available resources, and thus, education and outreach may help reduce financial burdens for this small, but vulnerable part of the population. Also, ensuring that all CSHCN have a medical home, per national recommendations, may reduce out‐of‐pocket expenses due to care coordination and decreasing unnecessary high cost, repetitive, or emergent interventions . Screening family members for mental health needs may be beneficial at pediatric visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members, however, may not be aware of all available resources, and thus, education and outreach may help reduce financial burdens for this small, but vulnerable part of the population. Also, ensuring that all CSHCN have a medical home, per national recommendations, may reduce out‐of‐pocket expenses due to care coordination and decreasing unnecessary high cost, repetitive, or emergent interventions . Screening family members for mental health needs may be beneficial at pediatric visits.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, financial and socioeconomic stressors explain more variation in the psychological impact on families than CHD severity. 25,26 Ensuring 29,30 Screening family members for mental health needs may be beneficial at pediatric visits. These types of caregiver screenings have already been established for the postpartum period, 31 and other types of childhood conditions.…”
Section: Although Some Cshcn Are Eligible To Be Covered Under State Cmentioning
confidence: 99%
“…[7][8][9][10] On the other hand, multiple large national PCMH evaluations 11 have shown mixed evidence of PCMH impacts on service access, quality, and cost. 8,[12][13][14][15][16][17][18][19] A meta-analysis of 11 PCMH studies, published between 2008 and 2014, showed that PCMH practices were significantly associated with a 1.5% reduction in specialty visits and an increase in cancer screenings (1.2% for cervical cancer and 1.4% for breast cancer). 12 Yet, these researchers also found a lack of association between PCMH and primary care, emergency department and inpatient visits, and several quality measures.…”
Section: Patient-centered Medical Home Modelmentioning
confidence: 99%
“…high heterogeneity across clinical settings and patient characteristics. 12,15,18,19 Although all are relevant, these explanations do not acknowledge that the effectiveness of complex health interventions, like PCMH, lies not only in the presence of strategies and activities but also on the core purposes that those activities are trying to achieve. 23 Across studies, there is an underlying assumption that the intervention is sufficiently robust that the researchers can estimate its effect while holding contextual factors constant, and that aspects of the intervention affect a single primary outcome.…”
Section: Key Constructs Within the Complex Health Intervention Frameworkmentioning
confidence: 99%
“…Interest in the medical home has increased with the passage of the landmark 2010 Patient Protection and A ordable Care Act, which designated substantial resources for demonstrating and evaluating medical homes across the nation. Nevertheless, the published evaluation studies have generated mixed evidence about the impacts of a medical home on health care utilization, costs and quality (Cohen et al, 1996;Bethell et al, 2004;Strickland et al, 2004;Damiano et al, 2006;Beal et al, 2009;Romaire and Bell, 2010;Stevens et al, 2010;Strickland et al, 2011;Han et al, 2017). Most utilization and cost outcomes did not differ significantly between patients with and without a medical home.…”
Section: Introductionmentioning
confidence: 99%